Comparison of continuous review system method and min-max method in soybean inventory control - Syafitri, Ellysa; Lubis, Riri Syafitri (Bulletin of Applied Mathematics and Mathematics Education, 2024)
This study aims to compare the effectiveness of two inventory control methods, namely continuous review system and min-max in controlling soybean raw material inventory in tofu production. The continuous review system method is an inventory control system where raw material inventory is checked continuously while the min-max method is a method that maintains raw materials between the minimum and maximum limits. The data used are data on soybean raw material inventory and needs at the Ali Musa tofu factory in Serdang Bedagai Regency, Indonesia. Based on the results of the analysis of total inventory costs using the continuous review system method, it is IDR 418,978,693 in 2021 and IDR 430,271,763 in 2022. While the total inventory cost using the min-max method is IDR 366,272,031 in 2021 and IDR 367,964,100 in 2022. While the company uses IDR 429,321,708 in 2021 and IDR 445,381,200 in 2022. From the calculations above, the min-max method is more effective in reducing total inventory costs with infrequent ordering frequencies. Since orders are not made regularly, this strategy reduces the number of soybean orders and reduces the cost of ordering. When the reorder limit is reached, the company will place the order. The choice of inventory control method must be adjusted to the needs and operational characteristics of the company. The continuous review system method is better for companies with high and fluctuating raw material needs, while min-max can be used for companies with more stable raw material needs. The findings and the method used in this study could be beneficial for the factory to organize its inventory efficiently.